2016
DOI: 10.1007/s00213-016-4391-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effect of menthol on nicotine self-administration in rats

Abstract: Rationale Tobacco smoking is a leading preventable cause of premature death in the United States. Menthol is a significant flavoring additive in tobacco products. Clinical evidence suggests that menthol may promote tobacco smoking and nicotine dependence. However, it is unclear whether menthol enhances the reinforcing actions of nicotine and thus facilitates nicotine consumption. This study employed a rat model of nicotine self-administration to examine the effects of menthol on nicotine-taking behavior. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 90 publications
(104 reference statements)
5
60
1
Order By: Relevance
“…However, in rats that had self-administered nicotine but did not receive pre-session menthol administration (menthol-naive subjects), menthol administration neither reinstated nicotine-seeking behavior nor interacted with the nicotine cue. These results extended a role of menthol in directly enhancing nicotine reinforcement, as demonstrated in our previous work (Biswas et al, 2016), to an interoceptive cueing effect of menthol on nicotine-seeking behavior. In contrast, menthol did not produce a similar effect in the rats trained to self-administer food with pre-session menthol administration.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, in rats that had self-administered nicotine but did not receive pre-session menthol administration (menthol-naive subjects), menthol administration neither reinstated nicotine-seeking behavior nor interacted with the nicotine cue. These results extended a role of menthol in directly enhancing nicotine reinforcement, as demonstrated in our previous work (Biswas et al, 2016), to an interoceptive cueing effect of menthol on nicotine-seeking behavior. In contrast, menthol did not produce a similar effect in the rats trained to self-administer food with pre-session menthol administration.…”
Section: Discussionsupporting
confidence: 89%
“…These findings suggest that menthol administration in smokers may set the occasion for nicotine intake and serve as a reminder of tobacco smoking, which would then facilitate nicotine seeking and trigger relapse. Together with other clinical and animal observations that showed that menthol may interact with nicotine to increase nicotine reinforcement (Ahijevych and Garrett, 2004; Ahijevych and Garrett, 2010; Alsharari et al, 2015; Biswas et al, 2016; Wang et al, 2014), these data indicate that menthol may significantly contribute to the initiation, progression, and relapse of tobacco smoking.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Menthol has also been shown to increase self-administration of nicotine (Biswas et al, 2016). However, we did not observe any menthol or nicotine-related differences in puffing behavior during the ad-lib period.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows evaluation of the aggregate effects of these constituents on EC abuse liability. This is important for understanding the abuse liability of ECs, because certain non-nicotine constituents in ECs (e.g., menthol, minor alkaloids) can enhance the addiction-related effects of nicotine, or can be behaviorally active themselves [2,4,13,14]. Because these models involve parenteral (e.g., i.v., s.c.) administration rather than inhalational exposure, they allow for the study of the addiction-related effects of EC constituents within the central nervous system (CNS), largely independent of their peripheral (e.g., sensory) effects.…”
Section: Introductionmentioning
confidence: 99%